Respon Ikan Lele Dumbo (Clarias gariepinus B) Terhadap Pakan Tepung Ikan, Tepung Maggot dan Tepung Media Maggot BSF Difermentasi IRS - Syahrizal, Syahrizal; Yulfiperius, Yulfiperius; Ghofur, Muarofah (Universitas Batangahari Jambi, 2026)
The food consumed is part of the body's active biochemical elements that are essential for fish growth. Therefore, various considerations are needed to provide fish with quality feed that meets their needs. Feed quality can be assessed by its protein content, which can be obtained from high-protein plant materials and the assistance of bacterial decomposers, as well as from the bioconversion of BSF maggots. This study aimed to analyze the effect of cattle rumen contents (IRS) on cassava leaf flour (Manihot utilissima), tarum leaf flour (Indigofera zollingeriana), and lamtoro leaf flour (Leucaena leucocepphala) to produce maggots. Maggot flour and the organic media from one 21-day cycle of BSF (Black Soldier Fly) flies were made into pellets supplemented with fish meal (TI) for African catfish (Clarias gariepinus B). A completely randomized design with 4 treatments and 3 replications was used, with treatment A (IRS 0.00%); B (IRS 5.0% : C (IRS 10.0%), D (IRS 15.0%). The observation results in the form of the average proximate protein of the best final organic maggot media raw materials in C and D were 30.75%; and 31.55%, respectively, the initial organic media protein was 20.00% and 20.15%. The best proximate pellet feed was also in C and D with 36.53% and 37.55% protein and 307.34 and 285.73 Kcal/100 grams of feed. The best maggot biomass in D (60.59 grams) followed by C (42.60 grams) with an ESE conversion value (organic substrate efficiency) in treatments A (5.49%), B (4.91%), C (7.10%) and D (10.10%). For the best average individual maggot weight in treatment A (0.26 grams/tail), followed by B (0.22 grams), the lowest D (0.18 grams/tail) and the best individual maggot length in treatment A (1.55 cm), followed by B (1.15 cm) and the lowest C (0.93 cm). The best individual maggot counts were C (1107 tails/600 grams) and D (969 tails/600 grams), followed by B (530 tails/600 grams) and A (526 tails/600 grams). The best absolute growth of catfish was the average individual weight in treatment D (106.01 grams) with the best SR level of 100%. The best FCR and EPP levels were in treatment D (1.18) and EPP (87.31%) with relatively good water quality parameters with a temperature of 24-26oC, pH 7.2-7.5, DO 5.2-5.8 ppm, and ammonia 0.009-0.012 ppm